Risk Analysis of Production Machinery Maintenance at PT. XYZ Uses Fuzzy Failure Mode and Effect Analysis Method - Dendi Hermawan; Aditia Ginantaka; Ahmad Syarbaini (Agroindustrial Technology Journal, 2024)
This research focuses on improving the performance of the blowing machine used for producing gallon bottle packaging. The blowing machine faces issues with the mold cover component not closing properly, triggering the locking mold alarm. To address this problem, a case study using the Six Big Losses method and a fishbone diagram helps identify the main factors causing downtime. Additionally, the researcher employs the F-FMEA method to identify the most likely failure modes of the blowing machine. The blowing machine experiences unplanned downtime totaling 2323 minutes, with an averaging74.94 minutes. The locking mold alarm is the main cause of downtime, resulting in a time loss of 1611 minutes. The F-FMEA calculation yields an FRPN value for the factors causing the locking mold alarm, with the dry/sticking pin mold receiving an FRPN value of 900 in rank 1, the small shaft not releasing receiving an FRPN value of 700 in rank 2, and the loose pin mold shaft bolt receiving an FRPN value of 333.33 in rank 3. Insufficient training on the blowing machine receives an FRPN value of 208.33 in rank 4. Improvement recommendations involve operational training, replacing the small shaft material from VCN-150 to SKD-11, enhancing maintenance of the pin shaft bolt, and providing regular lubrication